Substance use, psychosocial vulnerability, and resilience: Trends and predictors 2000-2022 in high school and college populations - Sariñana, Maria Elena Castro; Cuautli, Ema Morales; Pulido, Diana E. González; Padilla, María Guadalupe López; Torres, Pedro Leyva; López, Claudia Vanessa Rodríguez (Migration Letters, 2024)
Trends in substance use and psychosocial vulnerability are presented in a population of high school and college students in the period 2000/2022, during which 7 representative samples of students obtained with random selection methods were studied. In 2022, the sample size was 399 for high school and 321 for college. A risk model is used that assumes that, although experimental consumption in student populations is not addictive consumption, it is a risk and an indicator of the level of stress that students are suffering. This model of cumulative risk and psychosocial stress has also led to the design of a resilience-based model of protection. The research instrument was the Inventory of Risk-Protection for Adolescents (IRPA-II), allowing the elaboration of a specific diagnosis of psychosocial risk profiles and resilience factors, which is self-applicable, anonymous, and with closed and recoded questions. Its current application is online. The results present predictive models on psychosocial vulnerability and consumption variables and multivariate models to measure resilience levels in different groups. Substance use trends have decreased in both populations for Alcohol Tobacco and marijuana. Risk groups defined as those who use substances and report high psychosocial vulnerability were 5.7% in high school and 9.3% in college students. Selective prevention measures and contents applied within the University’s wellness programs are recommended, and recommendations of content and strategies for the implementation of such measures are detailed.